2010
DOI: 10.1002/jcp.22045
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of human equilibrative transporter 1 (hENT1) in patients with resected gastric cancer

Abstract: Nucleoside transporter proteins are specialized proteins that mediate the transport of nucleosides and nucleoside analog drugs across the plasma membrane. The human equilibrative nucleoside transporter 1 (hENT1) is a member of these proteins and mediates cellular entry of gemcitabine, cytarabine, and fludarabine. The hENT1 expression has been demonstrated to be related with prognosis and activity of gemcitabine-based therapy in breast, ampullary, lung, and pancreatic cancer. We investigated the immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…Several investigators have examined intratumoral hENT1 expression in various malignant tumors. According to these reports, the proportion of patients with high intratumoral hENT1 expression was 72% for breast cancer, 34 71% for lung cancer, 23 50% for bladder cancer, 22 45% for gastric cancer, 31 and 37% to 43% for pancreatic cancer. [24][25][26][27] With regard to biliary carcinoma, an Italian group reported that high intratumoral hENT1 expression was found in 63% of patients with ampullary cancer 35 and 68% of patients with biliary tract cancer, 28 although these reports were based on a small number of patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several investigators have examined intratumoral hENT1 expression in various malignant tumors. According to these reports, the proportion of patients with high intratumoral hENT1 expression was 72% for breast cancer, 34 71% for lung cancer, 23 50% for bladder cancer, 22 45% for gastric cancer, 31 and 37% to 43% for pancreatic cancer. [24][25][26][27] With regard to biliary carcinoma, an Italian group reported that high intratumoral hENT1 expression was found in 63% of patients with ampullary cancer 35 and 68% of patients with biliary tract cancer, 28 although these reports were based on a small number of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Santini et al 31 reported that in a retrospective analysis of 111 patients with resected gastric cancer who did not receive chemotherapy including gemcitabine, patients with high hENT1 expression had a shorter overall or disease-free survival than those with low hENT1 expression. In addition, they also reported a similar result in an immunohistochemical analysis of 41 tumors from patients with ampullary cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunohistochemistry of mCNT1-3 in mouse choroid plexus. IHC staining of formalin fixed paraffin embedded wild-type (FVB/N) mouse choroid plexus was undertaken using methods previously described [241]. The antibodies mCNT1 , mCNT2 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) and mCNT3 each reacted specifically on an immunoblot with a membrane isolate from yeast expressing the relevant nucleoside transporter (data not shown).…”
Section: Nucleoside Homeostasismentioning
confidence: 99%
“…At present, it has been considered that the occurrence of GC is closely related to Helicobacter pylori infection, gene mutation, diet, and other risk factors. [3][4][5] Despite much progress in the treatment of GC, the overall 5 year survival rate of patients with GC is still less than 30%. 6 Heterogeneity and a lack of effective therapeutic targets are the two major obstacles to the precise treatment of GC.…”
Section: 2mentioning
confidence: 99%